2011
DOI: 10.1161/hypertensionaha.111.180729
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Reveals Renin mRNA Overexpression in Human Hypertensive Kidneys and a Role for MicroRNAs

Abstract: Abstract-The kidney has long been invoked in the etiology of essential hypertension. This could involve alterations in expression of specific genes and microRNAs (miRNAs). The aim of the present study was to identify, at the transcriptome-wide level, mRNAs and miRNAs that were differentially expressed between kidneys of 15 untreated hypertensive and 7 normotensive white male subjects of white European ancestry. By microarray technology we found 14 genes and 11 miRNAs that were differentially expressed in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
188
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 219 publications
(202 citation statements)
references
References 31 publications
11
188
0
3
Order By: Relevance
“…[17] Importantly, binding of miR-181a to the 3'UTR of the renin gene was demonstrated using luciferase reporter assays transfected into HEK293 kidney cells. This clearly explains how miR181a may lead to decreased renin mRNA levels.…”
Section: Circulating Micrornas and Existing Mechanisms Of Blood Pressmentioning
confidence: 99%
“…[17] Importantly, binding of miR-181a to the 3'UTR of the renin gene was demonstrated using luciferase reporter assays transfected into HEK293 kidney cells. This clearly explains how miR181a may lead to decreased renin mRNA levels.…”
Section: Circulating Micrornas and Existing Mechanisms Of Blood Pressmentioning
confidence: 99%
“…(Table 1 -republished with permission [19]) Tissue used for analyses were chosen based on tissue-specific transcriptomic work performed in SHRs [20]. Renal tissue specifically consisted of renal cortex as mRNA is differentially expressed dependant on the type of renal tissue [21]. Approximately 100 mg (± 10 mg) of renal tissue was homogenised in 1 ml of TRI-reagent, using the TRI-reagent method (Sigma Aldrich, St. Louis, MO, USA).…”
Section: Exercise Protocolmentioning
confidence: 99%
“…15 Marques et al 15 showed that hypertensive individuals have marked underexpression of miR-181a in the kidney, accompanied by marked overexpression of renin mRNA. Such a pattern was seen in BPH/2J mice in our study.…”
Section: Is Reduced Mir-181a Mediating the Ren1 Overexpression And Hymentioning
confidence: 99%
“…14 We also measured the micro-RNA (miRNA) miR-181a because its human homolog has been shown to negatively regulate human renin mRNA and is reduced in the kidney in human hypertension. 15 Tyrosine hydroxylase (TH) staining, a marker of sympathetic innervation, 16 was used to quantify renal innervation.…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation